2021
DOI: 10.1126/science.abe0981
|View full text |Cite
|
Sign up to set email alerts
|

Early developmental asymmetries in cell lineage trees in living individuals

Abstract: Mosaic mutations can be used to track cell lineages in humans. We used cell cloning to analyze embryonic cell lineages in two living individuals and a postmortem human specimen. Of 10 reconstructed postzygotic divisions, none resulted in balanced contributions of daughter lineages to tissues. In both living individuals, one of two lineages from the first cleavage was dominant across tissues, with 90% frequency in blood. We propose that the efficiency of DNA repair contributes to lineage imbalance. Allocation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…Notably, a high fraction of indels occurred among the recessive lineage compared with the dominant lineage, which indicated that DNA repair efficiency contributed to this imbalanced lineage differentiation. Further analysis confirmed that most SNVs resulted from the consecutive deamination of 5-methylcytosine [ 46 ]. Another paper in the same issue of Science led by Peter J.…”
Section: New Single-cell Techniques Address Hsc Generation At Spatial and Temporal Resolutionsmentioning
confidence: 99%
“…Notably, a high fraction of indels occurred among the recessive lineage compared with the dominant lineage, which indicated that DNA repair efficiency contributed to this imbalanced lineage differentiation. Further analysis confirmed that most SNVs resulted from the consecutive deamination of 5-methylcytosine [ 46 ]. Another paper in the same issue of Science led by Peter J.…”
Section: New Single-cell Techniques Address Hsc Generation At Spatial and Temporal Resolutionsmentioning
confidence: 99%
“…Such mutations are likely present at a higher fraction of cells in a tissue, yet at a lower fraction than germline variant. For example, such mutations could occur during early development and be present in a high fraction of cells across tissues in the human body (6). The distribution of mutations (as dots) on a plane with axes corresponding to the two scores can be used to divide the calls into mosaic mutations, germline variants, noise or false positive (low mosaic and low germline score) and high frequency mosaic mutations (high mosaic and high germline score) (Fig.…”
Section: Conceptmentioning
confidence: 99%
“…2A&C), all mutations from All 2 , bulk, and pairwise comparison were used. For details, including calling mosaic mutation from bulk tissue and lineage tree construction please refer to the method section of Fasching et al (6).…”
Section: Mutation Calling For Lineage Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Somatic mutations naturally occur in proliferative and post-mitotic cells throughout human development and during aging, starting from the first cleavage of the zygote (1)(2)(3)(4). An open question is: how frequent are somatic mutations in the population, and are they a contributing factor to the etiology of neuropsychiatric disorders (5)?…”
Section: Introductionmentioning
confidence: 99%